Cardiac tissue engineering: A comparative analysis on microscaffold patterning. (December 2022) - Ibrahim, Fatimah; Thiha, Aung; Wan Kamarul Zaman, Wan Safwani; Kamarulzaman, Yusniza; Dahlan, Nuraina Anisa; Jamaluddin, Nurul Fauzani; Madou, Marc J.
Abstract: There is a growing interest in understanding the biological, physical, and chemical properties of materials in an attempt to innovate bioinspired scaffolds mimicking the native human extracellular matrix. In cardiac tissue engineering, bioinspired cardiac scaffolds could open a repertoire of alternative treatments for various stages of cardiac diseases. This review introduces a novel perspective on different microscaffold patterns and their technological applications in cardiac tissue engineering. This review will also discuss desirable scaffold properties such as anisotropy, mechanical, porosity, and elasticity which are influenced by material selection and architecture of the cardiac microscaffold. A comparative analysis of different microscaffold patterns (i.e . micropillar and microchannel, cross-linked grid, interwoven, honeycomb, ellipse, and sponge-like) presents current updates on the progress of six micropatterning technologies on the development of cardiac scaffolds. This review covers appropriate materials to engineer three-dimensional (3D) scaffolds including our insights on their potential for cardiac tissue engineering. We also highlight the current challenges to replicate the thick native heart and future outlook on microscaffold patterning in steering the future of cardiac tissue engineering. Graphical Abstract: ga1 Highlights: Importance of scaffold micropatterns on engineered cardiac tissue properties. Analysis of the various 3D microscaffold patterns and required parameters for biomimetic cardiac tissue engineering. Current limitations and future direction in cardiac tissue scaffold patterning.